Diagnosis dan Tatalaksana Terkini Penyakit Jantung Hipertensi - Moningka, Brigita L. M.; Rampengan, Starry H.; Jim, Edmond L. (e-CliniC, 2021)
Abstract: Hypertensive heart disease is a response to a prolonged increase in blood pressure that causes various changes in the myocardial structure. This study was aimed to obtain the recent diagnosis and management of hypertensive heart disease. This was a literature review study using 4 databases, as follows: Pubmed, Clinical Key, Science Direct, and Google Scholar. The keywords used were Hypertensive Heart Disease diagnosis of Hypertensive heart disease OR Screening of hypertensive heart disease OR imaging of hypertensive heart disease AND therapy OR treatment OR management of hypertensive heart disease. The results showed that there were 10 literatures that fulfilled the criteria, consisting of 6 randomized controlled trials and 4 article reviews. Among patients with hypertensive heart disease, left ventricle hypertrophy, left ventricular dilation, and diastolic and systolic disfunction were the most commonly found in ECG, echocardiography, chest X-ray, and CMR. Therapy of hypertensive heart disease was according to ACC/AHA guidelines with non-pharmacological therapy by adopting the DASH diet and pharmacological therapy of choice was ACE-I or ARB. In conclusion, in hypertensive heart disease, the most common structural changes were left ventricle hypertrophy, left ventricular dilation, diastolic and systolic disfunction found in ECG, echocardiography, chest X-ray, and CMR. Therapy of hypertensive heart disease was according to ACC/AHA guidelines.Keywords: hypertensive heart diseaseÂ Abstrak: Penyakit jantung hipertensi merupakan respon terhadap peningkatan tekanan darah berkepanjangan yang menyebabkan berbagai perubahan pada struktur miokard. Penelitian ini bertujuan untuk mendapatkan diagnosis dan tatalaksana terkini mengenai penyakit jantung hipertensi. Jenis penelitian ialah literature review menggunakan 4 database, yaitu Pubmed, Clinical Key, Science Direct, dan Google Scholar. Kata kunci yang digunakan ialah Hypertensive Heart Disease diagnosis of Hypertensive heart disease OR Screening of hypertensive heart disease OR imaging of hypertensive heart disease AND therapy OR treatment OR management of hypertensive heart disease. Hasil penelitian mendapatkan 10 literatur yang memenuhi kriteria penelitian, terdiri dari 6 randomized controlled trial dan 4 review article. Pada penyakit jantung hipertensi kelainan struktural yang sering ditemukan ialah hipertrofi ventrikel kiri (konsentrik maupun eksentrik), dilatasi ventrikel kiri, disfungsi diastolik dan sistolik, yang dapat dideteksi lewat pemeriksaan EKG, ekokardiografi, rontgen toraks, dan CMR. Terapi penyakit jantung hipertensi menurut pedoman ACC/AHA yakni nonfarmakologi seperti pola diet DASH dan terapi farmakologi pilihan yaitu ACE-I atau ARB. Simpulan penelitian ini ialah pada penyakit jantung hipertensi terdapat hipertrofi ventrikel kiri, dilatasi ventirkel kiri, disfungsi diastolik maupun sistolik, dideteksi menggunakan EKG, ekokardiografi, rontgen toraks dan CMR. Terapi penyakit jantung hipertensi sesuai dengan pedoman penatalaksanaan ACC/AHA.Kata kunci: penyakit jantung hipertensi